STUDY OF CHANGES IN CORAL REEFS COVER AT AYAU ARCHIPELAGO, RAJA AMPAT - Ayu Isma Yanti, Gusti
The Ayau Islands are in western Papua and part of the Raja Ampat Regency, Indonesia. The characteristic profile of coral reefs themselves are relatively flat and classified as very broad. This makes the area very vulnerable to changes in coral reefs due to erratic water conditions. This study aims to look at changes in coral reefs that have occurred from 2015 to 2019. By using Landsat 8 OLI satellite imagery and field data from the Nusa Manggala Expedition conducted by LIPI in 2018 was found that the condition of the area of coral reefs in the Ayau Islands growing far from the coast and classified into fringing coral reefs. From 2015 to 2016, the area of coral reefs has decreased area of 583.47 ha. From 2016 to 2018 the area of coral reefs also increased to an area of 1518.57 ha. From 2018 to 2019, the area of coral reefs decreased again by 1265.13 ha. From 2018 to 2019 the area of coral reefs has decreased again by covering an area of 1265.13 ha. One of these changes is influenced by changes in sea surface temperature with a change of 1-2 oC from its normal temperature and the rate of change in the area of coral reefs worth 66.006 ha / year. This is one of the effects of the El Niño-Southern Oscillation (ENSO) phenomenon in the eastern Pacific Ocean.